Gender division of household labor: How does culture operate? - Miriam Marcén; Marina Morales (Global Labor Organization (GLO), 2019)
In this paper, we examine whether culture plays a role in the gender division of household labor. To explore this issue, we use data on early-arrival first and second generation immigrants living in the United States. Since all these individuals have grown up under the same laws, institutions, and economic conditions, then the differences between them in the gender division of housework may be due to cultural differences. We find that the higher the culture of gender equality in the country of ancestry, the greater the equality in the division of housework. This is maintained when we consider both housework and childcare as household labor. Our work is extended by examining how culture operates and is transmitted. We study whether culture may influence by and with whom housework activities are performed and the timing of the day when this happens, which can help us to understand how culture operates in the family life of couples. Results indicate that the more culture of gender equality is associated with greater probability that individuals report performing housework when they are with their partner in the evening, which may improve family live by making housework a non-individual task. The cultural impact is also observed in the case of working days, but it is not so clear during public holidays, which can be explained by the fact that those individuals originating from less egalitarian countries work longer work hours than those from egalitarian countries.
Keywords: D13; J13; Z13; 330; Culture; immigrants; housework; childcare